Invention--Its relation to the farmer and farm laborer - Trembly, Elven Creveling (My University, 1895)
Introduction: We are more or less familiar with the crude tools and implements used by the tillers of the soil in times long gone by. We know of their forked stick and clam-shell hoes, and the difficulties which necessarily had to be overcome. Life was a continual drudge to them and were it not for natures store of food in the shape of wild game and fruit, the people must certainly have starved, or at least suffered untold misery. Time has brought great changes. The “inventive mind” has been continually occupied until today we have the greatly improved methods and machines by which the soil is turned, the seed planted, the growing plant tended, the golden grain harvested and sent to market. More than this, life has changed in every aspect; civilization has advanced and wandering tribes are fast decreasing; government has changed, business has flourished. Social and physical have been the changes. The inside as well as the outside of the farmer’s home has been beautified. Conveniences without number have been placed within his reach from time to time, but of the ones I wish to speak in particular are those which have been perfected within the last seventy-five or one hundred years.
Citation: Trembly, Elven Creveling. Invention--Its relation to the farmer and farm laborer. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Inventions; Farm equipment; Farm tools; Theses; Manuscripts (documents)